FRI0717-HPR Assessing the burden of treated and untreated chronic low back pain in europe. (12th June 2018) - Doane, M.J.; Jaffe, D.H.; Dragon, E.; Abraham, L.; Viktrup, L.; Bushmakin, A.G.; Cappelleri, J.C.
Abstract : Background: Chronic low back pain (CLBP) is estimated to affect about 20% of adults 1 and is the greatest contributor to disability globally. 2 Current pharmacological treatment options may provide limited pain relief or may not be appropriate for long-term use in all patients because of adverse events. 3 Despite the large burden of CLBP, few studies have evaluated the humanistic and economic impact of this condition in Europe, or whether this burden varies for those being treated with prescription (Rx) treatments compared with those who are not Rx treated. Objectives: To assess the burden of CLBP in Europe and to determine whether burden differs by pain severity and treatment status. Methods: A retrospective, cross-sectional study was conducted using data from the 2016 and 2017 National Health and Wellness Survey (NHWS) from five European Union countries (5EU): France, Germany, Italy, Spain, and United Kingdom. NHWS respondents with a self-reported CLBP diagnosis, current pain lasting ≥3 months, and who completed the pain module were identified. Neuropathic and phantom limb pains were excluded. CLBP respondents were categorized into 4 groups by severity of pain and treatment: moderate/severe Rx treated [M/S-Treated]; moderate/severe Rx untreated [M/S-Untreated]; mild Rx treated; and mild Rx untreated (reference). Outcomes of interest included health-related quality of life (HRQoL) (SF-12v2: mental and physical component summary [MCS, PCS]), health status (EQ-5D), productivity loss (Work Productivity and Activity Impairment [WPAI] questionnaire), and health care professional (HCP) visits in past 6 months. Multivariable analyses adjusted for baseline differences between groups (e.g., demographic and health characteristics). Results: A total of 2, 086 CLBP patients were identified from the NHWS. CLBP patients reported an average age of 56.4 (SD=13.2) years and most were female (61.2%). Two-thirds of CLBP patients had M/S pain (n=1, 403). Stratification by pain and treatment groups resulted in the following groups: M/S-Treated=29.8%, M/S-Untreated=37.4%, Mild-Treated=19.5%, and Mild-Untreated=13.2%. Increased pain severity among both treated and untreated patients showed significantly worse HRQoL, health status, work and activity impairment, and greater HCP visits compared with the reference group (Mild-Untreated) (table 1). Conclusions: Results suggest the majority of European patients with CLBP in this study had moderate to severe pain irrespective of treatment. Whether treated or untreated, those with moderate to severe pain demonstrated a substantial burden related to HRQoL, health status, overall work and activity impairment, and HCP visits compared with those with mild pain. References: 1. Meucci RD, et al. Rev Saude Publica2015;49:1–10. 2. GBD. Lancet2017;390(10100):1211–59. 3. Noble, M, et al. Cochrane Database Syst Rev. 2010;20(1):1–68. Disclosure of Interest: M. Doane Grant/research support from: Pfizer Ltd., D. Jaffe Grant/research support from: Pfizer Ltd., E. Dragon Employee of: Pfizer Ltd., L. Abraham Employee of: Pfizer Ltd., L. Viktrup Employee of: Eli Lilly & Company, A. Bushmakin Employee of: Pfizer Ltd., J. Cappelleri Employee of: Pfizer Ltd.